DEVELOPMENT OF INTRARETINAL CYSTOID LESIONS IN EYES WITH INTERMEDIATE AGE-RELATED MACULAR DEGENERATION. Issue 8 (August 2016) - Steinberg, Julia S.; Göbel, Arno P.; Thiele, Sarah; Fleckenstein, Monika; Holz, Frank G.; Schmitz-Valckenberg, Steffen
Abstract : Purpose: To evaluate the development of intraretinal cystoid lesions (ICLs) in eyes with intermediate age-related macular degeneration. Methods: Serial multimodal retinal imaging data of 105 eyes from 87 age-related macular degeneration subjects (median age of 75.0 years) with no late age-related macular degeneration at baseline from the prospective longitudinal natural history "molecular diagnostic of age-related macular degeneration-study" were included. The presence of ICLs—defined as lacunar hyporeflective areas within the neurosensory retina—was determined by spectral-domain optical coherence tomography at Month 24. Both baseline and further follow-up data were additionally evaluated. Results: At Month 24, ICLs were identified in 12 of 105 (11.7%) eyes of which 4 had developed signs of choroidal neovascularization since baseline. Intraretinal cystoid lesions in these four eyes with choroidal neovascularization were mostly found at the level of the outer nuclear layer. Intraretinal cystoid lesions in the remaining 8 eyes occurred mainly at the level of the inner nuclear layer, showed smaller horizontal and vertical dimensions, and were not spatially confined to an increase in retinal thickness. Conclusion: The results indicate that ICLs may develop also in the absence of active neovascularization. Distinctive morphologic features and localization of ICLs may be indicative of different underlying pathogenetic mechanisms. If no manifest choroidal neovascularization can be established in the presence of ICLs, close monitoring as well as awareness and self-monitoring seem to be advisable. Abstract : Supplemental Digital Content is Available in the Text.Intraretinal cystoid lesions associated with age-related macular degeneration may also develop in the absence of active neovascularization. Then, they are most frequently found at the level of the inner nuclear layer, show smaller horizontal and vertical dimensions, and are not associated with increased retinal thickness.